Perlindungan Hukum Terhadap Konsumen yang Dirugikan Atas Kelalaian Pelaku Usaha Cuci Sepatu di Denpasar Timur - I Wayan Indra Adi Wicaksana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2021)
Public interest in shoes is a special need, shoes are in great demand by millennials because they are useful for protecting feet. The habit of collecting these shoes arises from the desire of humans to keep their goods so they don't get damaged quickly and stay clean for a Long time. However, there are still cases of damage to shoes that cause Losses to consumers and there is no responsibility from the shoe washing service. The research method used is the type of empirical Law, empirical legal research aims to find facts, and conduct interviews. There are internal and external factors that cause damage to consumer shoes by business actors. So that responsibility for losses cannot be carried out unilaterally between business actors and consumers because there are Legal remedies that can be taken if they are harmed. Lack of knowledge and understanding fromconsumers, makes the position of consumers lower than business actors. So with the existence of Law Number 8 of 1999 concerning Consumer Protection, both parties need to know so that their rights and obligations are not violated.